How Does the Interactivity of Social Media Affect the Adoption of New Green Products? - Cao, Xin; Wu, Xitong; Huang, Xiaozhi (Frontiers in Psychology, 2021)
In the era of mobile internet, newsfeed advertising, which is most applicable to consumption scenarios that involve mobile devices, has become a core driving force in advertising. The rapid advancement of technology with respect to newsfeed advertising has not only reshaped the green consumption sector but has also had significant impacts on consumer psychology and behavior. When faced with highly social green newsfeed advertising, consumers are receptive to different degrees, which ultimately affects their receptivity to new green products. Through an experiment and a questionnaire, we find the following: (1) Consumers prefer new green products advertised through high-sociality green newsfeed advertisements more than those advertised with low-sociality ads. (2) Receptivity to green advertising can mediate the impact of the sociality of newsfeed advertising on consumer adoption of new green products. (3) The aforementioned direct effect and mediating effect are also affected by consumers’ green involvement. Our paper has both theoretical and practical significance; that is, we contribute to the research on the impacts of the sociality of green advertising on the psychological mechanisms underlying consumer adoption of new green products. Additionally, we provide managerial recommendations for the future development of green newsfeed advertising and for improvements in consumer impressions of green consumption.